Minimum age of marriage under Islamic law and the Islamic family law (Federal Territories) Act 1984: a preliminary study on an ideal age of marriage in Malaysia - Mohd, Azizah; A. Kadir, Nadhilah (2018)
Marriage is a sacred institution which goal is to achieve mutual cooperation and happiness among the parties. As a religious covenant, marriage is to be contracted based on several essential requirements and conditions. Under Islamic law, age factor is not listed as one of marriage requirement. There is no text of the Quran or the Sunnah that indicate certain specific age of marriage that may affect marriage validity. This lead to an understanding that there is no specific age of marriage under Islamic law. Nevertheless, the Muslim jurists are in agreement that a person is recommended to marry at the age where he or she understands the nature of the marriage contract, so that the marriage goal can be achieved. The issue arises as to what is the minimum age of marriage where a person is able to comprehend such marriage relationship. This paper seeks to primarily examine the issue of minimum age of marriage in Malaysia and the most suitable age of marriage under Islamic law that governs Muslims in Malaysia. Examination extends to juristic discourse on that matter and the incorporation of the Hanafis view and its significance in the minimum age of marriage that is recognized by the law in Malaysia. The research adopts qualitative research methodology where many of the materials will be based in the library. The research will provide suggestion for improvement of the law on minimum age of marriage in Malaysia where relevant and necessary.